Non-noble metal zinc oxide nanosheet photocatalyst as well as preparation method and application thereof

By doping non -precious metals on zinc oxide nanoscopic tablets, forming zinc oxide nano -catalysts rich in oxygen -rich nano -level, solving the problem of high methane oxide reaction temperature and low efficiency in existing technology, realizing efficient catalytic methane conversion at room temperature at room temperature For formaldehyde.

CN119368188APending Publication Date: 2025-01-28TAIYUAN UNIVERSITY OF TECHNOLOGY +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411514641.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing photocatalytic technology has high temperature requirements and low efficiency in the direct oxidation and conversion of methane into formaldehyde.

Method used

Using non -precious metal zinc oxide nanofatile photocatalysts, zinc acetate and urea ultrasonic treatment and microwave heating to form ZNO nanoscopic tablets, and use non -precious metals such as FE, CO, Ni, and CU by impregnation method to change the structure and performance of ZNO.

Benefits of technology

Active catalytic methane oxidation of formaldehyde is achieved at room temperature, which improves catalytic efficiency and production of formaldehyde, reduces the reaction temperature and energy consumption, and reduces the cost of catalyst at the same time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the technical field of photocatalytic methane conversion, and particularly relates to a non-noble metal zinc oxide nanosheet photocatalyst as well as a preparation method and application thereof. The preparation method comprises the following steps: S1, slowly dropwise adding a zinc acetate aqueous solution into a urea aqueous solution, carrying out ultrasonic treatment for 30 minutes, intensely stirring to fully dissolve the zinc acetate aqueous solution, transferring the mixture into a microwave reactor, heating, cooling, washing, and carrying out high-temperature roasting on a sample in an argon atmosphere after the sample is subjected to rotary evaporation drying; s2, dissolving the roasted sample in N-methyl-2-pyrrolidone, performing ice-water bath ultrasonic treatment on the mixture on an ultrasonic machine, and performing centrifugal drying to obtain ZnO nanosheets; s3, dissolving a non-noble metal precursor in deionized water, adding the ZnO nanosheet, uniformly stirring, and evaporating the solution to dryness by using a reduced pressure distillation rotary evaporator; and S4, transferring the sample to a muffle furnace for roasting, and cooling to room temperature to obtain the TM-ZnO sample. The preparation method is simple, the prepared catalyst is high in catalytic activity, and the conversion rate of directly converting methane into formaldehyde is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalytic methane conversion, and specifically relates to a non-noble metal zinc oxide nanosheet photocatalyst and a preparation method and application thereof. Background Art

[0002] Compared with coal and oil, natural gas releases less sulfide and nitride when burned, making it the cleanest fossil energy. With the continuous increase in proven reserves of natural gas, its main component, methane, has attracted widespread attention from researchers not only as a fuel but also as a chemical raw material. Natural gas is a gas at room temperature and pressure, and is mainly distributed in remote areas. It needs to be refrigerated at high pressure before it can be transported through pipelines, which increases the cost of natural gas. On the other hand, as a greenhouse gas, methane has a greenhouse effect that is more than 20 times that of carbon dioxide (CO2). Therefore, converting methane into a high-value chemical can not only reduce its transportation costs, but also has important significance for achieving environmental protection and dual carbon goals. As a derivative of methane, formaldehyde is an important precursor for the production of industrial resins and plastics, and is also widely used in the textile and pharmaceutical industries. Therefore, direct photocatalytic oxidation of methane to formaldehyde is more environmentally friendly and efficient, which is of great significance to environmental protection and dual carbon goals.

[0003] Chinese patent CN104710291A discloses a method for preparing formaldehyde by photocatalytic oxidation of methane, using a zinc-molybdenum oxide-loaded molecular sieve prepared by a hydrothermal method to photocatalytically oxidize methane to prepare formaldehyde. The reaction can be carried out at normal pressure, but the reaction temperature is 80-110°C, and heating is required during the reaction, resulting in large losses. Chinese patent CN111701590A discloses a Au x / cubic-WO3 photocatalyst and its application in the photocatalytic production of formaldehyde from methane. Although the gold-modified WO3 catalyst can directly convert methane into formaldehyde, the catalytic efficiency is low and the formaldehyde yield is relatively low. ZnO is an important ultraviolet light-responsive semiconductor material and is widely used in the field of photocatalytic technology. However, its inherent wide bandgap characteristics lead to the rapid recombination of photogenerated electrons and holes, and the relatively limited surface catalytic active sites, which together limit the photocatalytic efficiency of ZnO. Therefore, in order to overcome these limitations and improve its catalytic activity, researchers often need to perform various modifications on ZnO. Summary of the invention

[0004] The purpose of the present invention is to provide a non-precious metal zinc oxide nanosheet photocatalyst and a preparation method and application thereof, so as to solve the problems of high temperature requirement and low efficiency in the direct oxidation reaction of methane into formaldehyde in the existing photocatalytic technology.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A non-precious metal zinc oxide nanosheet photocatalyst has a structural formula of TM-ZnO; the non-precious metal loading is 0.025-1.0wt%, ZnO is a zinc oxide nanosheet with rich pore structure and oxygen vacancies, and the non-precious metals are Fe, Co, Ni and Cu.

[0007] The preparation method of the non-precious metal zinc oxide nanosheet photocatalyst comprises the following specific steps:

[0008] S1: Dissolve urea and zinc acetate in deionized water respectively and stir until completely dissolved. Slowly add the zinc acetate aqueous solution dropwise into the urea aqueous solution, ultrasonically treat for 30 minutes and then vigorously stir to fully dissolve it. Transfer the mixture to a microwave reactor for heating, cooling, and washing. After the sample is dried by rotary evaporation, place the sample in a tube furnace and calcine it at high temperature under an argon atmosphere.

[0009] S2: The calcined sample was dissolved in N-methyl-2-pyrrolidone, the mixture was sonicated in an ultrasonic machine using an ice-water bath, and centrifuged to dry to obtain ZnO nanosheets;

[0010] S3: Dissolve 475-19000 μL of non-precious metal precursor in 10-60 mL of deionized water, add 2-20 g of ZnO nanosheets and stir evenly, and then evaporate the solution to dryness using a vacuum distillation rotary evaporator;

[0011] S4: The sample was transferred to a muffle furnace and calcined for 4 h. After the product was cooled to room temperature, a TM-ZnO sample was obtained.

[0012] Furthermore, the molar ratio of urea to zinc acetate in step S1 is (1-3.5):1.

[0013] Furthermore, in the step S1, the heating temperature in the microwave oven reactor is 100-200° C., the power is 300 W, and the continuous heating time is 5-10 hours, the high temperature roasting temperature is 400-700° C., and the continuous heating time is 5-10 hours.

[0014] Furthermore, in step S2, the concentration of the mixture is 5-10 mg / mL, the ultrasonic frequency is 60-100 W for 1-3 h, and the centrifugal speed is 2-6 krpm for 0.5-2 h.

[0015] Furthermore, the non-precious metal precursor in step S3 is any one of chlorides, nitrates and sulfates of Fe, Co, Ni and Cu.

[0016] Furthermore, the non-noble metal precursor was dissolved in 60 mL of deionized water, and 10 g of ZnO nanosheets was added.

[0017] Furthermore, the calcination temperature in step S4 is 300-600°C.

[0018] Principle of catalyst preparation:

[0019] Zinc acetate and urea are dissolved in water to form a mixed solution. Zinc acetate provides a zinc source, while urea serves as a precipitant and structure-directing agent. Microwave heating can provide rapid and uniform heating, which is conducive to the formation of a uniform ZnO structure. Under high temperature conditions, urea decomposes to produce ammonia (NH3) and carbon dioxide (CO2). Ammonia reacts with water to form ammonium hydroxide (NH4OH), which increases the pH value of the solution and provides an alkaline environment for the precipitation of ZnO. In an alkaline environment, the zinc ions (Zn 2+ ) and hydroxide ions (OH - ) to generate ZnO precipitate; N-methyl-2-pyrrolidone as an organic solvent is a structure-directing agent that affects the crystal growth and morphology of ZnO. 2+ The ions form complexes, affecting the nucleation and growth process of the crystal, thereby controlling the morphology and size of ZnO; after the reaction is completed, N-methyl-2-pyrrolidone and other impurities in the reaction mixture are removed by centrifugation, filtration and washing to obtain pure ZnO nanosheets; the non-precious metal precursor is dissolved in deionized water, ZnO nanosheets are added and stirred evenly, and the non-precious metal ions enter the ZnO lattice through physical mixing and subsequent heat treatment processes to achieve doping. The doped sample is calcined in a muffle furnace for 4 hours, which helps to stabilize the distribution of non-precious metal ions in the ZnO lattice and further improve the crystallinity and phase purity of the material.

[0020] Non-precious metal zinc oxide nanosheet photocatalyst is a zinc oxide nanosheet doped with oxygen vacancies, which shows the potential for application as a photocatalyst in the photocatalytic methane oxidation reaction, effectively promoting the separation of photogenerated carriers, accelerating the rate of in-situ generation of H2O2, and greatly improving the conversion rate of H2O2 to ·OH, while improving the photocatalytic efficiency and reducing the peroxidation of the target product, and can be used for photocatalytic methane oxidation to formaldehyde. The specific steps of application are:

[0021] Take 5-30 mg of the catalyst and dissolve it in 10-30 mL of deionized water using an ultrasonic method. Oxygen is used as an oxidant, the oxygen pressure is 0-1 MPa, the methane pressure is 0.1-3 MPa, the total pressure is 0.1-3 MPa, and the light source is a xenon lamp with a wavelength range of 350-780 nm. The reaction is carried out at room temperature and reacts for 1-6 hours under the irradiation of the xenon lamp, and the content of the gas and liquid products is detected.

[0022] The detection methods of gas phase products and liquid phase products include:

[0023] Gas chromatography (GC): used to detect CO, CO2, CH3OH, CH3CH2OH, CH3COOH, etc.

[0024] Ion chromatography (IC): used to detect HCOOH, etc.

[0025] Acetylacetone colorimetric method: used to detect HCHO.

[0026] Furthermore, the volume ratio of methane to oxygen is 28:2.

[0027] Reaction mechanism of catalytic oxidation of methane to formaldehyde:

[0028] The doping of non-precious metals causes an increase in oxygen vacancies on ZnO. Electrons migrate from the conduction band to the oxygen vacancies of ZnO and then continue to transfer to the non-precious metals. At this time, O2 is adsorbed on the non-precious metal sites and is reduced by electrons to generate O2 - , then O2 - It is reduced to H2O2 by electrons, and H2O2 is quickly decomposed into ·OH; the reduction path of O2 is O2→·O2 - →H2O2→·OH, the conversion rate of this step from H2O2→·OH is high. The main function of the holes remaining in the valence band is to oxidize H2O in the reaction system to ·OH; CH4 is mainly oxidized to ·CH3 by ·OH produced by the reduction of O2, and then ·CH3 continues to react with ·OH to generate CH3OH, which is quickly oxidized to HCHO; the role of non-precious metals and oxygen vacancies is that they are both electron acceptors, and the synergistic effect of non-precious metals and oxygen vacancies promotes the efficient separation of electrons and holes during the reaction.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The catalyst is mainly obtained by doping non-precious metals into the ZnO lattice through the impregnation method, which causes the change of the ZnO lattice parameter. The interaction between the non-precious metals and ZnO is stronger, and the catalyst is more stable.

[0031] (2) The preparation method adds N-methyl-2-pyrrolidone, which promotes the nucleation and growth process of the crystal, thereby controlling the morphology and size of ZnO, and the zinc oxide nanosheets obtained by rotary evaporation drying are more uniform, which can improve the reaction activity;

[0032] (3) The photocatalyst prepared by the preparation method can carry out the photocatalytic methane oxidation reaction to formaldehyde at room temperature, and the conditions are mild; secondly, under light conditions, oxygen is used as the oxidant, which is more economical and environmentally friendly;

[0033] (4) The preparation method doped non-precious metals into porous zinc oxide nanosheets with abundant oxygen vacancies, changing the structure of zinc oxide. Among them, iron doping has the most obvious effect on the photocatalytic methane oxidation activity of zinc oxide. Iron doping narrows the band gap of zinc oxide and increases its visible light utilization rate. In addition, the addition of iron increases the amount of H2O2 generated, and the Fenton effect of iron causes H2O2 to be quickly decomposed into active oxygen species OH, promoting the activation and conversion of methane.

[0034] (5) The preparation method of the photocatalyst is simple and easy to operate. At the same time, the prepared catalyst has strong catalytic activity, a high conversion rate of methane directly converted to formaldehyde, and increased formaldehyde production. It has broad application prospects in the photocatalytic methane to formaldehyde reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 XRD diagrams of the photocatalysts of Example 1, Example 2, Example 3, Example 4 and Comparative Example 1;

[0036] Figure 2 The XRD patterns of Example 5, Example 6, Example 7, Example 8, Example 9, Example 10, Example 11, and Comparative Example 1;

[0037] Figure 3 The EPR spectra of the photocatalysts of Example 1 and Comparative Example 1;

[0038] Figure 4 The Raman spectra of the photocatalysts of Example 1 and Comparative Example 1 are shown;

[0039] Figure 5 is the AC-STEM image of the photocatalyst of Example 1;

[0040] Figure 6 It is a comparison chart of the yield and selectivity of photocatalytic methane oxidation to formaldehyde in Example 1, Example 2, Example 3, Example 4 and Comparative Example 1;

[0041] Figure 7 It is a comparison chart of the yield and selectivity of formaldehyde produced by photocatalytic methane oxidation at different loading ratios of Example 1, Example 5, Example 6, Example 7, Example 8, Example 9 and Example 10;

[0042] Figure 8 This is a comparison chart of the yield and selectivity of formaldehyde produced by photocatalytic methane oxidation at different total pressures of Example 1, Example 11, Example 12 and Example 13;

[0043] Fig. 9 A comparison chart of the yield and selectivity of formaldehyde produced by photocatalytic methane oxidation at different gas ratios in Example 1, Example 14, Example 15, Example 16 and Example 17;

[0044] Fig.10 This is a comparison chart of the yield and selectivity of formaldehyde produced by photocatalytic methane oxidation with different water amounts in Example 1, Example 18, Example 19 and Example 20;

[0045] Fig.11 This is a comparison chart of the yield and selectivity of formaldehyde produced by photocatalytic methane oxidation with different catalyst masses in Example 1, Example 21, Example 22 and Example 23;

[0046] Fig.12 The comparison diagrams of Example 1, Example 24, Example 25, Example 26, Example 27, Example 28 and Example 29 show the changes in the yield and selectivity of formaldehyde produced by photocatalytic methane oxidation at different reaction times. DETAILED DESCRIPTION

[0047] The technical solution of the present invention is clearly and completely described below in conjunction with the accompanying drawings and embodiments.

[0048] Example 1

[0049] 3.4 g of zinc acetate and 4.25 g of urea were ultrasonically dissolved in 20 mL of deionized water. The zinc acetate solution was slowly added dropwise to the urea solution. After ultrasonic treatment for 30 min, it was vigorously stirred to fully dissolve. The mixture was transferred to a microwave reactor for heating. After the solution cooled to room temperature, it was centrifuged and washed three times with deionized water and ethanol respectively. After the product was dissolved, it was rotary evaporated and dried at 50 ° C for 1 h to obtain a solid mixture. The obtained solid mixture was then placed in a tube furnace and heated at 2 ° C min under an argon atmosphere. -1 The temperature was raised to 500°C at a heating rate and calcined at this temperature for 10 hours. The calcined sample was dissolved in N-methyl-2-pyrrolidone, the mixture concentration was 10 mg / mL, the ultrasonic frequency was 90 W, the ultrasonic time was 1 hour, and then centrifuged at a centrifugal speed of 3 krpm for 0.5 hours. Zinc oxide nanosheets were obtained after drying; 950 μL of FeCl3·6H2O was dissolved in 60 mL of deionized water, and then 10 g of ZnO nanosheets were added. The solution was evaporated to dryness using a reduced pressure distillation rotary evaporator, and the sample was transferred to a muffle furnace and calcined at 400°C for 4 hours. The product was cooled to room temperature to obtain Fe 0.05 -ZnO sample. Take 10 mg of the catalyst and dissolve it in 30 mL of deionized water by ultrasonic. Fill it with methane and oxygen at a ratio of 28:2. The total pressure is 3 MPa. The reaction temperature is 25 °C. The light source is a xenon lamp with a wavelength range of 350-780 nm. The reaction is carried out for 1 hour. The formaldehyde yield is 29.00 μmol / h -1 , the formaldehyde selectivity is 89.45%, (HCHO selectivity = HCHO production / (HCHO+HCOOH+CO2) production).

[0050] Example 2

[0051] 3.4 g of zinc acetate and 4.25 g of urea were ultrasonically dissolved in 20 mL of deionized water. The zinc acetate solution was slowly added dropwise to the urea solution. After ultrasonic treatment for 30 min, it was vigorously stirred to fully dissolve. The mixture was transferred to a microwave reactor for heating. After the solution cooled to room temperature, it was centrifuged and washed three times with deionized water and ethanol respectively. After the product was dissolved, it was rotary evaporated and dried at 50 ° C for 1 h to obtain a solid mixture. The obtained solid mixture was then placed in a tube furnace and heated at 2 ° C min under an argon atmosphere. -1 The temperature was raised to 500°C at a heating rate and calcined at this temperature for 10 hours. The calcined sample was dissolved in N-methyl-2-pyrrolidone, the mixture concentration was 10 mg / mL, the ultrasonic frequency was 90W, the ultrasonic time was 1 hour, and then centrifuged at a centrifugal speed of 3krpm for 0.5 hours. Zinc oxide nanosheets were obtained after drying. 950μL of CoCl2·6H2O was dissolved in 60mL of deionized water, and then 10g of ZnO nanosheets were added. The solution was evaporated to dryness using a vacuum distillation rotary evaporator, and the sample was transferred to a muffle furnace and calcined at 400°C for 4 hours. After the product was cooled to room temperature, Co 0.05 -ZnO sample. Take 10 mg of the catalyst and dissolve it in 30 mL of deionized water by ultrasonic. Fill it with methane and oxygen at a ratio of 28:2. The total pressure is 3 MPa. The reaction temperature is 25 °C. The light source is a xenon lamp with a wavelength range of 350-780 nm. The reaction is carried out for 1 hour. The formaldehyde yield is 12.03 μmol / h -1 , the formaldehyde selectivity is 82.12%.

[0052] Example 3

[0053] 3.4 g of zinc acetate and 4.25 g of urea were ultrasonically dissolved in 20 mL of deionized water. The zinc acetate solution was slowly added dropwise to the urea solution. After ultrasonic treatment for 30 min, it was vigorously stirred to fully dissolve. The mixture was transferred to a microwave reactor for heating. After the solution cooled to room temperature, it was centrifuged and washed three times with deionized water and ethanol respectively. After the product was dissolved, it was rotary evaporated and dried at 50 ° C for 1 h to obtain a solid mixture. The obtained solid mixture was then placed in a tube furnace and heated at 2 ° C min under an argon atmosphere. -1The temperature was raised to 500°C at a heating rate and calcined at this temperature for 10 hours. The calcined sample was dissolved in N-methyl-2-pyrrolidone, the mixture concentration was 10 mg / mL, the ultrasonic frequency was 90W, the ultrasonic time was 1 hour, and then centrifuged at a centrifugal speed of 3krpm for 0.5 hours. Zinc oxide nanosheets were obtained after drying. 950μL of NiCl2·6H2O was dissolved in 60mL of deionized water, and then 10g of ZnO nanosheets were added. The solution was evaporated to dryness using a vacuum distillation rotary evaporator, and the sample was transferred to a muffle furnace and calcined at 400°C for 4 hours. After the product was cooled to room temperature, Ni 0.05 -ZnO sample. Take 10 mg of the catalyst and dissolve it in 30 mL of deionized water by ultrasonic. Fill it with methane and oxygen at a ratio of 28:2, the total pressure is 3 MPa, the reaction temperature is 25 ° C, and react for 1 hour under the irradiation of a xenon lamp with a wavelength range of 350-780 nm. The formaldehyde yield is 9.21 μmol / h -1 , the formaldehyde selectivity is 84.96%.

[0054] Example 4

[0055] 3.4 g of zinc acetate and 4.25 g of urea were ultrasonically dissolved in 20 mL of deionized water. The zinc acetate solution was slowly added dropwise to the urea solution. After ultrasonic treatment for 30 min, it was vigorously stirred to fully dissolve. The mixture was transferred to a microwave reactor for heating. After the solution cooled to room temperature, it was washed by centrifugation and washed three times with deionized water and ethanol respectively. After the product was dissolved, it was dried by rotary evaporation at 50 ° C for 1 h to obtain a solid mixture. The obtained solid mixture was then placed in a tube furnace and heated at 2 ° C min under an argon atmosphere. -1 The temperature was raised to 500°C at a heating rate and calcined at this temperature for 10 hours. The calcined sample was dissolved in N-methyl-2-pyrrolidone, the mixture concentration was 10 mg / mL, the ultrasonic frequency was 90W, the ultrasonic time was 1 hour, and then centrifuged at a centrifugal speed of 3krpm for 0.5 hours. Zinc oxide nanosheets were obtained after drying. 950μL of CuCl2·2H2O was dissolved in 60mL of deionized water, and then 10g of ZnO nanosheets were added. The solution was evaporated to dryness using a vacuum distillation rotary evaporator, and the sample was transferred to a muffle furnace and calcined at 400°C for 4 hours. The product was cooled to room temperature to obtain Cu 0.05 -ZnO sample. Take 10 mg of the catalyst and dissolve it in 30 mL of deionized water by ultrasonic. Fill it with methane and oxygen at a ratio of 28:2. The total pressure is 3 MPa. The reaction temperature is 25 °C. The reaction is carried out under the irradiation of a xenon lamp with a wavelength range of 350-780 nm for 1 hour. The formaldehyde yield is 6.16 μmol / h -1 , the formaldehyde selectivity is 80.97%.

[0056] Example 5

[0057] 475 μL of FeCl3·6H2O was dissolved in 60 mL of deionized water, and then 10 g of ZnO nanosheets was added. The solution was evaporated to dryness using a vacuum distillation rotary evaporator. The sample was transferred to a muffle furnace and calcined at 400 °C for 4 h. After the product was cooled to room temperature, Fe 0.025 -ZnO sample. Take 10 mg of the catalyst and dissolve it in 30 mL of deionized water by ultrasonic. Fill it with methane and oxygen at a ratio of 28:2. The total pressure is 3 MPa. The reaction temperature is 25 °C. The reaction is carried out under the irradiation of a xenon lamp with a wavelength range of 350-780 nm for 1 h. The formaldehyde yield is 13.01 μmol / h -1 , the formaldehyde selectivity is 84.53%.

[0058] Example 6

[0059] 1900 μL of FeCl3·6H2O was dissolved in 60 mL of deionized water, and then 10 g of ZnO nanosheets was added. The solution was evaporated to dryness using a vacuum distillation rotary evaporator. The sample was transferred to a muffle furnace and calcined at 400 °C for 4 h. The product was cooled to room temperature to obtain Fe 0.1 -ZnO sample. Take 10 mg of the catalyst and dissolve it in 30 mL of deionized water by ultrasonic. Fill it with methane and oxygen at a ratio of 28:2. The total pressure is 3 MPa. The reaction temperature is 25 ° C. The reaction is carried out under the irradiation of a xenon lamp with a wavelength range of 350-780 nm for 1 hour. The formaldehyde yield is 22.65 μmol / h -1 , the formaldehyde selectivity is 87.92%.

[0060] Example 7

[0061] 5700 μL of FeCl3·6H2O was dissolved in 60 mL of deionized water, and then 10 g of ZnO nanosheets was added. The solution was evaporated to dryness using a vacuum distillation rotary evaporator. The sample was transferred to a muffle furnace and calcined at 400 °C for 4 h. After the product was cooled to room temperature, Fe 0.3 -ZnO sample. Take 10 mg of the catalyst and dissolve it in 30 mL of deionized water by ultrasonic. Fill it with methane and oxygen at a ratio of 28:2. The total pressure is 3 MPa. The reaction temperature is 25 °C. The reaction is carried out under the irradiation of a xenon lamp with a wavelength range of 350-780 nm for 1 hour. The formaldehyde yield is 16.64 μmol / h -1 , the formaldehyde selectivity is 86.53%.

[0062] Example 8

[0063] 9500 μL of FeCl3·6H2O was dissolved in 60 mL of deionized water, and then 10 g of ZnO nanosheets was added. The solution was evaporated to dryness using a vacuum distillation rotary evaporator. The sample was transferred to a muffle furnace and calcined at 400 °C for 4 h. After the product was cooled to room temperature, Fe 0.5-ZnO sample. Take 10 mg of the catalyst and dissolve it in 30 mL of deionized water by ultrasonic. Fill it with methane and oxygen at a ratio of 28:2. The total pressure is 3 MPa. The reaction temperature is 25 °C. The reaction is carried out under the irradiation of a xenon lamp with a wavelength range of 350-780 nm for 1 h. The formaldehyde yield is 11.22 μmol / h -1 , the formaldehyde selectivity is 85.00%.

[0064] Example 9

[0065] 13300 μL of FeCl3·6H2O was dissolved in 60 mL of deionized water, and then 10 g of ZnO nanosheets was added. The solution was evaporated to dryness using a vacuum distillation rotary evaporator. The sample was transferred to a muffle furnace and calcined at 400 °C for 4 h. The product was cooled to room temperature to obtain Fe 0.7 -ZnO sample. Take 10 mg of the catalyst and dissolve it in 30 mL of deionized water by ultrasonic. Fill it with methane and oxygen at a ratio of 28:2. The total pressure is 3 MPa. The reaction temperature is 25 °C. The reaction is carried out under the irradiation of a xenon lamp with a wavelength range of 350-780 nm for 1 hour. The formaldehyde yield is 9.51 μmol / h -1 , the formaldehyde selectivity is 83.79%.

[0066] Example 10

[0067] 19000 μL of FeCl3·6H2O was dissolved in 60 mL of deionized water, and then 10 g of ZnO nanosheets was added. The solution was evaporated to dryness using a vacuum distillation rotary evaporator. The sample was transferred to a muffle furnace and calcined at 400 °C for 4 h. The product was cooled to room temperature to obtain Fe 1.0 -ZnO sample. Take 10 mg of the catalyst and dissolve it in 30 mL of deionized water by ultrasonic. Fill it with methane and oxygen at a ratio of 28:2. The total pressure is 3 MPa. The reaction temperature is 25 °C. The reaction is carried out under the irradiation of a xenon lamp with a wavelength range of 350-780 nm for 1 h. The formaldehyde yield is 7.53 μmol / h -1 , the formaldehyde selectivity is 88.28%.

[0068] Comparative Example 1

[0069] 3.4 g of zinc acetate and 4.25 g of urea were ultrasonically dissolved in 20 mL of deionized water. The zinc acetate solution was slowly added dropwise to the urea solution. After ultrasonic treatment for 30 min, the mixture was vigorously stirred to fully dissolve. The mixture was transferred to a microwave reactor for heating. After the solution was cooled to room temperature, it was centrifuged and washed three times with deionized water and ethanol respectively. After the product was dissolved, it was rotary evaporated and dried at 50 ° C for 1 h to obtain a solid mixture. The obtained solid mixture was placed in a tube furnace under an argon atmosphere at 2 ° C min -1The temperature was raised to 500°C at a heating rate and calcined at a constant temperature for 10 hours. The calcined sample was dissolved in N-methyl-2-pyrrolidone, the mixture concentration was 10 mg / mL, the ultrasonic frequency was 90 W, the ultrasonic time was 1 hour, and then centrifuged at a centrifugal speed of 3 krpm for 0.5 hours. Zinc oxide nanosheets were obtained after drying. 10 mg of the catalyst was ultrasonically dissolved in 30 mL of deionized water, filled with methane and oxygen at a ratio of 28:2, the total pressure was 3 MPa, the reaction temperature was 25°C, and the reaction was carried out under the irradiation of a xenon lamp with a light source wavelength range of 350-780 nm for 1 hour. The formaldehyde yield was 7.48 μmol / h -1 , the formaldehyde selectivity is 80.60%, (HCHO selectivity = HCHO production / (HCHO+HCOOH+CO2) production).

[0070] Figure 1 The XRD diagrams of the photocatalysts of Example 1, Example 2, Example 3, and Example 4 and Comparative Example 1 are shown in FIG. Figure 1 As shown in Figure 1, the crystal structure of the catalyst was analyzed by XRD. The XRD results of samples doped with different metals showed that all samples had only the diffraction peak of zinc oxide (PDF#36-1451). When Cu, Ni, Co, and Fe were added to ZnO, the characteristic peak (36.32°) of the ZnO (101) crystal plane shifted to a lower angle. Therefore, Cu, Ni, Co, and Fe atoms entered the ZnO lattice and were doped. No diffraction peaks of the corresponding metals and metal oxides were observed in the XRD diagram of the catalyst, which was due to the small amount of metal added.

[0071] Figure 2 The XRD diagrams of different iron loadings of Example 5, Example 6, Example 7, Example 8, Example 9, Example 10, Example 11, and Comparative Example 1 show that as the amount of iron added increases, the characteristic peak (36.32°) of the ZnO (101) crystal plane gradually shifts to a lower angle. Therefore, some Fe atoms enter the ZnO lattice and doping occurs. When the Fe doping amount is 0-0.3wt%, as the Fe addition amount increases, the characteristic peak (36.32°) of the ZnO (101) crystal plane shifts more significantly. When the Fe doping amount is 0.3-1.0wt%, the characteristic peak does not shift, proving that when the doping amount is 0.3wt%, Fe doping reaches saturation. No diffraction peaks of Fe species are observed, which is due to the small amount of Fe added.

[0072] Figure 3 The EPR spectra of the photocatalysts of Example 1 and Comparative Example 1 are as follows: Figure 3 As shown, ZnO and Fe 0.05 -ZnO have obvious characteristic peaks at g = 2.003, which are attributed to oxygen vacancies (Ov), indicating that oxygen vacancies exist in both catalysts. 0.05The Ov signal peak intensity of -ZnO is significantly higher than that of ZnO, indicating that Fe 0.05 The oxygen vacancy content of -ZnO is higher than that of ZnO, therefore, Fe doping is beneficial to the generation of oxygen vacancies in ZnO. Figure 4 The Raman spectra of the photocatalysts of Example 1 and Comparative Example 1 show the relative abundance of ZnO and Fe. 0.05 -ZnO at 580cm -1 The E1(LO) peak at indicates the presence of oxygen vacancies, and Fe 0.05 The E1(LO) peak of -ZnO is significantly stronger than that of ZnO.

[0073] Figure 5 The AC-TEM image of Example 1 shows that after iron doping of zinc oxide nanosheets, ZnO still maintains a porous sheet structure, proving that iron doping does not change the morphology of ZnO. Many bright spots are observed, corresponding to the uniformly dispersed iron atoms on ZnO.

[0074] Comparative Example 2

[0075] Using the data of Chinese patent CN111701590A, take 10mgAu 0.3 / - cubic WO3 catalyst was dispersed in 80mL H2O, filled with methane and oxygen at a ratio of 19:1, and a total pressure of 2MPa. Under full spectrum irradiation, the reaction was carried out for 3h at a reaction temperature of 25℃, and the formaldehyde yield was 3.83μmolh -1 (11487.7 μmol g -1 ×10mg×10 -3 ÷3h=3.829μmolh -1 ), the selectivity is close to 100%.

[0076] Figure 6 The yield and selectivity of the photocatalysts for photocatalytic methane oxidation to formaldehyde in Example 1, Example 2, Example 3, Example 4 and Comparative Example 1 are compared. After one hour of illumination, Fe 0.05 -ZnO has a higher formaldehyde yield of 29.00 μmolh -1 , the formaldehyde selectivity is 89.45%. Compared with Comparative Example 2, although the selectivity of the photocatalyst prepared by the present invention is slightly lower, the formaldehyde output is significantly higher than that of Comparative Example 2.

[0077] Figure 7 The yield and selectivity of photocatalytic methane oxidation to formaldehyde in different loading ratios of Example 1, Example 5, Example 6, Example 7, Example 8, Example 9, and Example 10 are compared. With the increase of Fe loading, the yield and selectivity of formaldehyde gradually increase. When the Fe addition amount is 0.05wt%, the yield of formaldehyde is 29.00μmol·h-1 , the selectivity of formaldehyde is 89.45%. As the doping amount of Fe continues to increase, the yield of formaldehyde gradually decreases. Therefore, the optimal doping amount of Fe is 0.05wt%.

[0078] Embodiment 11

[0079] Take 10mgFe 0.05 -ZnO was ultrasonically dissolved in 30 mL of deionized water, filled with methane and oxygen at a ratio of 28:2, a total pressure of 0.5 MPa, a reaction temperature of 25 °C, and reacted for 1 h under the irradiation of a xenon lamp with a wavelength range of 350-780 nm. The formaldehyde yield was 3.98 μmol / h -1 , the formaldehyde selectivity is 78.98%.

[0080] Example 12

[0081] Take 10mgFe 0.05 -ZnO was ultrasonically dissolved in 30 mL of deionized water, filled with methane and oxygen at a ratio of 28:2, with a total pressure of 1 MPa and a reaction temperature of 25 °C. The reaction was carried out for 1 h under the irradiation of a xenon lamp with a wavelength range of 350-780 nm. The formaldehyde yield was 7.45 μmol / h -1 , the formaldehyde selectivity is 85.53%.

[0082] Example 13

[0083] Take 10mgFe 0.05 -ZnO was ultrasonically dissolved in 30 mL of deionized water, filled with methane and oxygen at a ratio of 28:2, a total pressure of 2 MPa, a reaction temperature of 25 ° C, and reacted for 1 h under the irradiation of a xenon lamp with a wavelength range of 350-780 nm. The formaldehyde yield was 10.28 μmol / h -1 , the formaldehyde selectivity is 89.08%.

[0084] Figure 8 The figure is a comparison of the yield and selectivity of formaldehyde produced by photocatalytic methane oxidation at different total pressures of Example 1, Example 11, Example 12, and Example 13. As the reaction pressure increases, the solubility of methane and oxygen in water also increases. Therefore, the conversion rate of methane increases with the increase of pressure, and when the total pressure is 3MPa, the activity of photocatalytic methane oxidation is better.

[0085] Embodiment 14

[0086] Take 10mgFe 0.05 -ZnO was ultrasonically dissolved in 30 mL of deionized water, filled with methane and oxygen at a ratio of 29:1, with a total pressure of 3 MPa and a reaction temperature of 25 °C. The reaction was carried out under the irradiation of a xenon lamp with a wavelength range of 350-780 nm for 1 h, and the formaldehyde yield was 6.41 μmol / h -1, the formaldehyde selectivity is 79.32%.

[0087] Embodiment 15

[0088] Take 10mgFe 0.05 -ZnO was ultrasonically dissolved in 30 mL of deionized water, filled with methane and oxygen at a ratio of 27:3, with a total pressure of 3 MPa and a reaction temperature of 25 °C. The reaction was carried out for 1 h under the irradiation of a xenon lamp with a wavelength range of 350-780 nm. The formaldehyde yield was 20.69 μmol / h -1 , the formaldehyde selectivity is 89.76%.

[0089] Example 16

[0090] Take 10mgFe 0.05 -ZnO was ultrasonically dissolved in 30 mL of deionized water, filled with methane and oxygen at a ratio of 26:4, with a total pressure of 3 MPa and a reaction temperature of 25 °C. The reaction was carried out under the irradiation of a xenon lamp with a wavelength range of 350-780 nm for 1 h, and the formaldehyde yield was 17.95 μmol / h -1 , the formaldehyde selectivity is 87.39%.

[0091] Embodiment 17

[0092] Take 10mgFe 0.05 -ZnO was ultrasonically dissolved in 30 mL of deionized water, filled with methane and oxygen at a ratio of 24:6, with a total pressure of 3 MPa and a reaction temperature of 25 °C. The reaction was carried out under the irradiation of a xenon lamp with a wavelength range of 350-780 nm for 1 h, and the formaldehyde yield was 13.24 μmol / h -1 , the formaldehyde selectivity is 86.99%.

[0093] Fig. 9 The yield and selectivity comparison of formaldehyde produced by photocatalytic methane oxidation with different gas ratios in Example 1, Example 14, Example 15, Example 16, and Example 17 are shown. Due to the change in the partial pressure of methane and oxygen, the dissolved amounts of methane and oxygen in water are affected. When the methane-oxygen ratio is 28:2, the photocatalytic methane oxidation performance is better, and the formaldehyde yield is 29.00 μmol / h -1 , the formaldehyde selectivity is 89.45%.

[0094] Embodiment 18

[0095] Take 10mgFe 0.05 -ZnO was ultrasonically dissolved in 10 mL of deionized water, filled with methane and oxygen at a ratio of 28:2, a total pressure of 3 MPa, a reaction temperature of 25 °C, and reacted for 1 h under the irradiation of a xenon lamp with a wavelength range of 350-780 nm. The formaldehyde yield was 10.68 μmol / h -1 , the formaldehyde selectivity is 87.32%.

[0096] Embodiment 19

[0097] Take 10mgFe 0.05 -ZnO was ultrasonically dissolved in 20 mL of deionized water, filled with methane and oxygen at a ratio of 28:2, with a total pressure of 3 MPa and a reaction temperature of 25 °C. The reaction was carried out under irradiation with a xenon lamp with a wavelength range of 350-780 nm for 1 h, and the formaldehyde yield was 17.41 μmol / h -1 , the formaldehyde selectivity is 91.78%.

[0098] Embodiment 20

[0099] Take 10mgFe 0.05 -ZnO was ultrasonically dissolved in 25 mL of deionized water, filled with methane and oxygen at a ratio of 28:2, with a total pressure of 3 MPa and a reaction temperature of 25 °C. The reaction was carried out for 1 h under the irradiation of a xenon lamp with a wavelength range of 350-780 nm. The formaldehyde yield was 23.00 μmol / h -1 , the formaldehyde selectivity is 91.09%.

[0100] Fig.10 The yield and selectivity comparison of formaldehyde produced by photocatalytic methane oxidation with different water amounts in Example 1, Example 18, Example 19, and Example 20. As the amount of water in the reactor increases, the mass transfer of the reaction increases, and the yield of formaldehyde increases. The increase in water amount can also prevent product overoxidation. When the amount of Fe 0.05 -ZnO has better photocatalytic methane oxidation performance.

[0101] Embodiment 21

[0102] Take 2mgFe 0.05 -ZnO was ultrasonically dissolved in 30 mL of deionized water, filled with methane and oxygen at a ratio of 28:2, with a total pressure of 3 MPa and a reaction temperature of 25 °C. The reaction was carried out under the irradiation of a xenon lamp with a wavelength range of 350-780 nm for 1 h, and the formaldehyde yield was 7.75 μmol / h -1 , the formaldehyde selectivity is 85.92%.

[0103] Embodiment 22

[0104] Take 5mgFe 0.05 -ZnO was ultrasonically dissolved in 30 mL of deionized water, filled with methane and oxygen at a ratio of 28:2, with a total pressure of 3 MPa and a reaction temperature of 25 °C. The reaction was carried out under the irradiation of a xenon lamp with a wavelength range of 350-780 nm for 1 h, and the formaldehyde yield was 10.71 μmol / h -1 , the formaldehyde selectivity is 86.72%.

[0105] Embodiment 23

[0106] Take 20mgFe 0.05 -ZnO was ultrasonically dissolved in 30 mL of deionized water, filled with methane and oxygen at a ratio of 28:2, with a total pressure of 3 MPa and a reaction temperature of 25 °C. The reaction was carried out under the irradiation of a xenon lamp with a wavelength range of 350-780 nm for 1 h, and the formaldehyde yield was 15.36 μmol / h -1 , the formaldehyde selectivity is 88.73%.

[0107] Fig.11 The yield and selectivity comparison diagram of photocatalytic methane oxidation to formaldehyde with different catalyst masses of Example 1, Example 21, Example 22, and Example 23, with the increase of the amount of catalyst, the formaldehyde yield increases accordingly. When the catalyst dosage is 10 mg, the formaldehyde yield is relatively large, and the formaldehyde yield decreases instead when the catalyst dosage is further increased. When the catalyst dosage in the solution is too little, because the free radicals generated during the reaction are small and the methane conversion is low, the formaldehyde yield is low. When the catalyst dosage is too much, the light transmittance of the reaction system decreases, resulting in a decrease in the light absorption efficiency of the catalyst, and the final formaldehyde yield is also low.

[0108] Embodiment 24

[0109] Take 10mgFe 0.05 -ZnO was ultrasonically dissolved in 30 mL of deionized water, filled with methane and oxygen at a ratio of 28:2, a total pressure of 3 MPa, a reaction temperature of 25 ° C, and reacted for 0.5 h under the irradiation of a xenon lamp with a light source wavelength range of 350-780 nm. The formaldehyde yield was 7.41 μmol and the formaldehyde selectivity was 88.96%.

[0110] Embodiment 25

[0111] Take 10mgFe 0.05 -ZnO was ultrasonically dissolved in 30 mL of deionized water, filled with methane and oxygen at a ratio of 28:2, a total pressure of 3 MPa, a reaction temperature of 25 ° C, and reacted for 2 hours under the irradiation of a xenon lamp with a light source wavelength range of 350-780 nm. The formaldehyde yield was 34.66 μmol and the formaldehyde selectivity was 88.31%.

[0112] Embodiment 26

[0113] Take 10mgFe 0.05 -ZnO was ultrasonically dissolved in 30 mL of deionized water, filled with methane and oxygen at a ratio of 28:2, a total pressure of 3 MPa, a reaction temperature of 25 ° C, and reacted for 3 hours under the irradiation of a xenon lamp with a light source wavelength range of 350-780 nm. The formaldehyde yield was 51.97 μmol and the formaldehyde selectivity was 90.30%.

[0114] Embodiment 27

[0115] Take 10mgFe0.05 -ZnO was ultrasonically dissolved in 30 mL of deionized water, filled with methane and oxygen at a ratio of 28:2, a total pressure of 3 MPa, a reaction temperature of 25 ° C, and reacted for 4 hours under the irradiation of a xenon lamp with a wavelength range of 350-780 nm. The formaldehyde yield was 59.13 μmol and the formaldehyde selectivity was 91.29%.

[0116] Embodiment 28

[0117] Take 10mgFe 0.05 -ZnO was ultrasonically dissolved in 30 mL of deionized water, filled with methane and oxygen at a ratio of 28:2, a total pressure of 3 MPa, a reaction temperature of 25 ° C, and reacted for 5 hours under the irradiation of a xenon lamp with a light source wavelength range of 350-780 nm. The formaldehyde yield was 58.49 μmol and the formaldehyde selectivity was 89.15%.

[0118] Embodiment 29

[0119] Take 10mgFe 0.05 -ZnO was ultrasonically dissolved in 30 mL of deionized water, filled with methane and oxygen at a ratio of 28:2, a total pressure of 3 MPa, a reaction temperature of 25 ° C, and reacted for 6 hours under the irradiation of a xenon lamp with a light source wavelength range of 350-780 nm. The formaldehyde yield was 51.07 μmol and the formaldehyde selectivity was 84.79%.

[0120] Fig.12 The output and selectivity comparison diagram of the photocatalytic methane oxidation to formaldehyde at different reaction times of Example 1, Example 24, Example 25, Example 26, Example 27, Example 28, and Example 29, with the increase of reaction time, the formaldehyde and formic acid yields increase accordingly. When the reaction time is equal to 4h, the formaldehyde yield is high (59.13μmol), and the selectivity is 91.29%. Continue to increase the reaction time, the formaldehyde yield gradually decreases, and the formic acid output increases. With the increase of reaction time, the formaldehyde yield in the solution gradually increases, and the reaction rate of CH4 conversion to formaldehyde is gradually less than the rate of over-oxidation of formaldehyde to formic acid, resulting in a gradual decrease in the formaldehyde yield and an increase in the formic acid yield.

[0121] The zinc oxide nanosheets prepared by the simple ultrasonic exfoliation method of the present invention realize the uniform loading of non-precious metals by vacuum distillation and rotary evaporation. Compared with precious metals, the catalytic cost is significantly reduced while the catalytic performance is improved. The addition of Fe reduces the band gap of zinc oxide and increases its visible light utilization rate. On the other hand, the addition of iron increases the amount of H2O2 generated, and the Fenton effect of Fe causes H2O2 to be quickly decomposed into active oxygen species OH, promoting the activation and conversion of methane. Under the optimal reaction conditions, the yield of formaldehyde is 29.00 μmolh -1 , the selectivity of formaldehyde is 89.45%.

[0122] The above description is only a preferred embodiment of the present invention and does not constitute any other form of limitation to the present invention. Any modification or equivalent change made based on the technical essence of the present invention still falls within the scope of protection required by the present invention.

Claims

1. A non-precious metal zinc oxide nanosheet photocatalyst, characterized in that: The structural formula is TM-ZnO; the non-precious metal loading is 0.025~1.0wt%, ZnO is zinc oxide nanosheets with rich pore structure and oxygen vacancies, and the non-precious metals are Fe, Co, Ni and Cu.

2. The method for preparing a non-noble metal zinc oxide nanosheet photocatalyst according to claim 1, characterized in that: The specific steps are as follows: S1: Dissolve urea and zinc acetate in deionized water respectively and stir until completely dissolved. Slowly add the zinc acetate aqueous solution dropwise into the urea aqueous solution, ultrasonically treat for 30 minutes and then vigorously stir to fully dissolve it. Transfer the mixture to a microwave reactor for heating, cooling, and washing. After the sample is dried by rotary evaporation, place the sample in a tube furnace and calcine it at high temperature under an argon atmosphere. S2: The calcined sample was dissolved in N-methyl-2-pyrrolidone, the mixture was sonicated in an ultrasonic machine using an ice-water bath, and centrifuged to dry to obtain ZnO nanosheets; S3: Dissolve 475-19000 μL of non-precious metal precursor in 10-60 mL of deionized water, add 2-20 g of ZnO nanosheets and stir evenly, and then evaporate the solution to dryness using a vacuum distillation rotary evaporator; S4: The sample is transferred to a muffle furnace and calcined for 4 hours at a temperature of 300-600°C. After the product is cooled to room temperature, a TM-ZnO sample is obtained.

3. The method for preparing a non-precious metal zinc oxide nanosheet photocatalyst according to claim 2, characterized in that: The molar ratio of urea to zinc acetate in step S1 is (1-3.5):

1.

4. The method for preparing a non-noble metal zinc oxide nanosheet photocatalyst according to claim 3, characterized in that: In the step S1, the heating temperature in the microwave oven reactor is 100-200° C., the power is 300 W, and the continuous heating time is 5-10 hours. The high-temperature roasting temperature is 400-700° C., and the continuous heating time is 5-10 hours.

5. The method for preparing a non-noble metal zinc oxide nanosheet photocatalyst according to claim 4, characterized in that: In step S2, the concentration of the mixture is 5-10 mg / mL, the ultrasonic frequency is 60-100 W for 1-3 h, the centrifugal speed is 2-6 krpm for 0.5-2 h.

6. The method for preparing a non-precious metal zinc oxide nanosheet photocatalyst according to claim 5, characterized in that: The non-precious metal precursor in step S3 is any one of chlorides, nitrates and sulfates of Fe, Co, Ni and Cu.

7. The method for preparing a non-precious metal zinc oxide nanosheet photocatalyst according to claim 6, characterized in that: The non-noble metal precursor in step S3 is dissolved in 60 mL of deionized water, and 10 g of ZnO nanosheets is added.

8. The use of a non-precious metal zinc oxide nanosheet photocatalyst as claimed in claim 1, characterized in that: It is used for photocatalytic methane direct oxidation to produce formaldehyde. The specific steps are as follows: take 5~30 mg of the catalyst, dissolve it in 10~30 mL of deionized water by ultrasonic method, use oxygen as the oxidant, the oxygen pressure is 0~1MPa, the methane pressure is 0.1~3MPa, the total pressure is 0.1~3MPa, the light source is a xenon lamp with a wavelength range of 350-780nm, the reaction is carried out at room temperature, the reaction is carried out under the irradiation of the xenon lamp for 1~6 hours, and the content of the gas and liquid products is detected.

9. The use of a non-precious metal zinc oxide nanosheet photocatalyst according to claim 8, characterized in that: The volume ratio of methane to oxygen is 28:2.

Citation Information

Patent Citations

  • Method for preparing formaldehyde by methane photocatalytic oxidation

    CN104710291A

  • Aux / cubic WO3 photocatalyst and application of Aux / cubic WO3 photocatalyst in preparation of formaldehyde by photocatalysis of methane

    CN111701590A

  • Oxide-supported noble metal monoatomic catalyst and preparation method and application thereof

    CN110038549A

  • Supported zinc oxide catalyst as well as preparation method and application thereof

    CN114618469A

  • Molecular sieve photo-thermal catalyst for preparing methanol through methane oxidation and preparation method thereof

    CN118594601A